Resenha: MESQUITA, Léa Nilce (org.). Talupa/ Lixeratura: 30 anos. Belo Horizonte: Formato, 1998. (Revista do Centro de Estudos Portugueses, 1999)
Resenha: MESQUITA, Léa Nilce (org.). Talupa/ Lixeratura: 30 anos. Belo Horizonte: Formato, 1998.